Mencegah Kecanduan Game Online pada Remaja melalui Pola Asuh Orangtua - Ramot Sirait; Juliana Hindradjat; Yuseva Sariati (Universitas Malahayati Lampung, 2025)
ABSTRACT Online gaming among adolescents is a significant issue for families and communities. Adolescents allocate excessivetime to online gaming, resulting in adverse consequences. Time allocated for study is squandered, adversely affecting academic performance. Adolescents exhibit diminished capacity for socializing with peers. Prevention is essential to avert adolescent addiction. Parents must be vigilant on parenting patterns to prevent their children from developing an addiction to online games. This essay seeks to elucidate effective parenting strategies that can help teenagers prevent internet gaming addiction. This magazine employs a qualitative methodology by examining materials from books and prior research publications. Democratic parenting styles are the most effective within families due to the presence of communication and transparency between parents and children. Keywords: Game Online, Adolescents, Addiction, Parenting Strategies Patterns. ABSTRAK Game online di kalangan remaja telah menjadi masalah yang signifikan bagi keluarga dan masyarakat. Remaja menghabiskan waktu bermain game online hingga menimbulkan dampak negatif. Waktu belajar yang terbuang berdampak pada prestasi di sekolah. Remaja mengalami kesulitan dalam bersosialisasi dengan teman-teman. Perlu dilakukan pencegahan agar remaja tidak terjerumus ke dalam kecanduan. Pola asuh orang tua merupakan aspek penting yang harus diperhatikan agar anak tidak terjerat kecanduan permainan daring. Artikel ini bertujuan untuk menjelaskan metode pengasuhan yang efektif bagi orang tua dalam mencegah remaja dari kecanduan permainan daring. Metode yang digunakan dalam jurnal ini adalah metode kualitatif yang menganalisis materi dari buku dan jurnal penelitian sebelumnya. Pola asuh demokratis adalah yang paling optimal dalam keluarga karena mendorong komunikasi dan keterbukaan antara orang tua dan anak. Kata Kunci : Game Online, Remaja, Kecanduan, Pola Asuh Orangtua